Livelihood Activities of Rural Women Beneficiaries of Swarna Jayanti Swarozgar Yojna (SGSY) Programme - Ajay Singh , Alka Singh , Sanjay Singh; K K Singh (Indian Journal of Extension Education, 2018)
Women comprise half of human resources and have been identified as key agents of sustainable development and women’s equality is as central to a more holistic approach towards establishing new patterns and process of development that are sustainable. Women empowerment is the most important instrument for the socio-economic development of a nation. Bringing women into the mainstream is one of the major challenges for every government. In this context, Self - Help Groups (SHGs) have emerged as the tool that wield power to create a socio- economic revolution in the rural areas of our country. The Swarna Janyanti Gram Swarozgar Yojana (SGSY), a centrally sponsored Scheme of the Ministry of Rural Development, is a holistic programme covering all aspects of self employment and empowerment of rural women. The present investigation was carried out in Rewa district of M.P., to study the changes occurred in livelihood activities of rural women beneficiaries of Swarna Jayanti Gram Swarozgar Yojna (SGSY) programme. Overall mean sustainable livelihood index of beneficiaries of SGSY and non beneficiaries was 38.75 and 21.62 respectively. out of 200 beneficiaries, 46.50 per cent had medium extent of the sustainable livelihood, while 29.00 per cent respondents had low extent of the sustainable livelihood, and remaining 24.50 per cent showed high extent of the sustainable livelihood